Mattering, social support, resilience and sense of empowerment during the pandemic - Grace Jee Ern Nga; Daryl Kurian; Kususanto Ditto Prihadi; Abdul Aziz (International Journal of Public Health Science (IJPHS), 2022)
The sense of empowerment had always been reported as contingent upon resilience, the sense of financial security, and perceived social support (PSS). In the context of the Malaysian urban population, the outbreak shifted social dynamics through the enforcement of movement control order (MCO), a partial-to-full lockdown policy enforced by the government to curb the virus. Studies in the local context suggested that the implementation of MCO led to a sense of uncertainty towards social support and financial security among the population, as well as the decline of resilience and the sense of mattering. This sparked a question, whether the significance of PSS, resilience, mattering, and income levels are still significant in predicting the sense of empowerment among our population. Through open social media pages, 405 adults between 18 and 62 years of age (M=25.44) living in urban areas of Malaysia to respond to the scales of empowerment, resilience, PSS, and mattering with some financial compensation in the form of e-wallet credits. Our findings suggested that PSS was no longer a significant predictor of empowerment after controlling for resilience, mattering, and income, which was opposed to other predictors in the equation that were still significant even after controlling for each other. Further relationships among the variables, implications and suggestions are discussed.